2021
DOI: 10.9734/ijpss/2021/v33i2130670
|View full text |Cite
|
Sign up to set email alerts
|

Response of Gas Exchange Activity and Relative Water Content of Neem in Relation to Weather

Abstract: Neem is known for its medicinal values and is a hardy plant that can grow in a wide variety of environmental conditions. However, productivity is impacted by unfavourable weather conditions due to different geographical locations. The present study was conducted to study the influence of prevailing weather conditions on certain physiological parameters deciding the reproductive ability of neem trees. The study was conducted in two different locations at different agro-climatic regions of Tamil Nadu, India. Gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…When the transpiration rate increases, the gas exchange activities tend to increase but based on the other environmental conditions like soil moisture status, temperature, relative humidity the photosynthetic rate may increase or decrease. The present study supported by had already been reported in [14] that weather variables such as rainfall and temperature affect photosynthesis, transpiration, and Stomatal conductance in neem tree.…”
Section: Correlationsupporting
confidence: 91%
See 1 more Smart Citation
“…When the transpiration rate increases, the gas exchange activities tend to increase but based on the other environmental conditions like soil moisture status, temperature, relative humidity the photosynthetic rate may increase or decrease. The present study supported by had already been reported in [14] that weather variables such as rainfall and temperature affect photosynthesis, transpiration, and Stomatal conductance in neem tree.…”
Section: Correlationsupporting
confidence: 91%
“…Similar observation was found by [13]. In general, the transpiration rate had a positive association with photosynthesis and was an indirect indication of the rate of photosynthesis in leaves [14].…”
Section: Transpiration Ratesupporting
confidence: 85%
“…These findings are in line with Sajjadinia et al, (2010) in Pistachio trees, who inferred that the variation in temperature and solar radiation between the pre-flowering and flowering phases may likely to contribute the observed differences in RWC. Pugazenthi et al, (2021) inferred that rainfall during the flowering would increase the RWC of neem trees.…”
Section: Relative Water Content (Rwc)mentioning
confidence: 99%
“…Among weather parameters, rainfall positively influences RWC and temperature influences the gas exchange activities which favourably influenced the flowering, fruit formation and yield of neem trees (Pugazenthi et al, 2021). Results indicated that the soil moisture (SM) favoured the positive physiological responses that favouring neem tree flowering and reduced the stress inducing proline content.…”
Section: Correlation Between Weather and Physiological Responses Of N...mentioning
confidence: 99%
See 1 more Smart Citation